ZnO nanoparticles as sensing materials with high gas response for detection of n-butanol gas - Wang Zhezhe; Hongchao Shang; Rongjun ZHao; Xinxin Xing; Yude Wang (Journal of Nanostructures, 2017)
The high crystallinity ZnO nanoparticles with an average particle diameter 30 nm have been successfully synthesized with a surfactant-mediated method. The cationic surfactant (cetyltrimethylammonium bromide, CTAB) and the hydrous metal chlorides (ZnCl2⋅2H2O) appear to be the good candidates for obtaining a high yield of nanoparticles. The structural and morphological characterizations were carried out by X-ray powder diffraction, scanning electron microscope and transmission electron microscopy, respectively. The resulting powders are highly crystalline and largely monodisperse ZnO nanoparticles. When used as a sensing material in gas sensor, it exhibits the high-performance gas sensing performances including high gas response, good selectivity, fast response/recovery time, good repeatability as well as stability towards low-ppm-level (10 to 100 ppm) n-butanol gas. At the optimal operating temperature (260 ºC), its gas response toward 100 ppm butanol is 174.8. The response and recovery time are 18 and 11 seconds, respectively. Theses findings not only provide a novel approach to fabricate ZnO nanoparticles via a surfactant-mediated method, but also explore a promising gas sensor towards n-butanol.